O-101 Neospermatogenesis benefits from a three-dimensional culture system. (6th August 2021) - Lawrence, S; Haddad, M; Rosenwaks, Z; Palermo, G D
Abstract: Study question: Does a three-dimensional (3D) culture system increase the efficiency of male germline differentiation of mouse embryonic stem cells (mESC) over a bidimensional method? Summary answer: Our 3D culture system based on direct spherification proves superior to the standard bidimensional plating in promoting neogametogenesis of mESC into post-meiotic male germ cells. What is known already: Two-dimensional monolayer cell cultures are common in stem cell research. However, this method does not replicate a physiological 3D spatial relationship and may provide an inaccurate replication of in vivo environments. A 3D spherical structure allows us to mimic the seminiferous tubule, the site of in vivo spermatogenesis. By using spheroids as a scaffold to replicate cell culture systems, we can study spermatogenesis in a controlled setting. Direct spherification, a technique commonly used in molecular gastronomy, provides an opportunity to create spheroids that mimic in vivo events that materialize in the lab Study design, size, duration: mESCs were initially cultured on a 6-well plate coated with fibroblasts and inserted into sodium alginate spheres. To coax differentiation, spheres (3 to 6 mm in diameter) were plunged directly into differentiation medium (DM) while the control mESC in 6-well dishes were layered with it. Cells obtained from both culture systems were tested by biomarkers for different germ cell stages Participants/materials, setting, methods: Bidimensional mESC at 80% confluence were differentiated either on a plate or spherified for a 3D culture. Both systems underwent the same timeline of exposure to EpiLC medium with Activin A, bFGF and KSR for 3 days and PGCLC medium with BMP4, LIF, SCF and EGF for 7 days. Differentiated cells were retrieved from each method at day 3 and day 10 to assess for germ line differentiation markers, DAZL, VASA and BOULE Main results and the role of chance: Under optic visualization through the sphere wall, cellular aggregation was seen on day 2 of culturing in EpiLC medium while this phenomenon was not observed on bidimensional plating. In the conventional method, cells expressed 7% DAZL (spermatogonium cell stage) and 1% VASA (pre-spermatid cell stage) whereas in direct spherification, cells expressed 20% DAZL ( P < 0.001) and 15% VASA positivity ( P < 0.0001). To further compare the different methods in later stages of germ-line differentiation, the remaining spheres were cultured in PGCLC medium for 7 days. At day 10, isolated cells were assessed for VASA and DAZL again. In the conventional method, 23% of cells expressed positivity for VASA and 29% DAZL whereas direct spherification achieved a positivity rate of 43% for VASA ( P < 0.005) and 45% for DAZL ( P < 0.005). This increased expression in both VASA and DAZL signify the increased number of cells undergoing germline differentiation. Additionally, BOULE was assessed for the presence of meiotic cells such as the spermatocyte. The conventional method yielded < 1% BOULE positivity whereas in direct spherification, there was 10% positivity ( P < 0.005 ). Direct spherifcation result shows that differentiation almost doubled in comparison to the conventional method, yielding more post-meiotic cells in the same amount of time Limitations, reasons for caution: Despite a higher differentiation rate in direct spherification, these cells would still need to be tested for their fertilization potential. The ability to achieve fertilization, blastocysts and live pups would provide final proof and reliability of this method of neogametogenesis Wider implications of the findings: Differentiating ESCs through direct spherification provides an alternative to studying intercellular relationships. This provides an opportunity to study spermatogenesis in more detail by replicating the microenvironment of the seminiferous tubule. Once embryo developmental competence of the de novo gamete is confirmed, this may open a new chapter in human reproduction Trial registration number: N/A